PERMASALAHAN UMUM YANG DIALAMI ANAK JALANAN - M. Harwansyah Sinaga; Sri Yani; Ella Salsabila; Hasanah Hasibuan; Dinda Febriyanti Sinaga (STKIP Subang, 2023)
Street children are children who spend a lot of time on the streets starting from their daily activities or just wandering around to make a living from one place to another. The purpose of this study is to find out what underlies street children to decide to go down and live on the streets, what are the views of the community about street children, what are the problems experienced by street children. The research method used is descriptive qualitative by conducting interviews and observations of street children and the community concerned. Research location on Jl. Hero Character, Kec. Medan Perjuangan, Medan City which involved 6 people with 3 street children and 3 people from the community. The results of research on street children that the authors get are social problems that are an interesting phenomenon in social life. The author can meet children who spend most of their lives on the streets at various points in the center of the crowd in big cities, such as markets, terminals, stations, traffic lights, urban centers, and so on. Their street life is mainly related to economic activities, including busking, begging, selling, porters, delivering newspapers, cleaning cars, and so on. Although there are also groups of children who just hang around or gather aimlessly on the streets.